Control Methods Using Cross-Coupling Effects for Suppression of Rotor/Stator Rubbing System - Shang Zhiyong; Zhang Haiying; Shaymurat Talgar (MATEC Web of Conferences, 2015)
This paper investigated the influence of cross-coupling effects on the rubbing-related dynamics of rotor/stator systems, The stability analysis on the synchronous full annular rub solution of a rotor/stator system, which includes both the dynamics of the stator and the deformation on the contact surface as well as the cross-coupling terms in velocities and displacements, is carried out. It is found that some cross-coupling effects will benefit the synchronous full annular rubs and some will not. Based on the finding, a control method by generating cross-coupling damping on the stator through the active auxiliary bearing is then proposed in order to suppress the contact severity and avoid the rubbing instability. Numerical simulation shows the validity of the mehtod.